The impact of glacier geometry on meltwater plume structure and submarine melt in Greenland fjords. Issue 18 (29th September 2016) - Carroll, D.; Sutherland, D. A.; Hudson, B.; Moon, T.; Catania, G. A.; Shroyer, E. L.; Nash, J. D.; Bartholomaus, T. C.; Felikson, D.; Stearns, L. A.; Noël, B. P. Y.; van den Broeke, M. R.
Abstract: Meltwater from the Greenland Ice Sheet often drains subglacially into fjords, driving upwelling plumes at glacier termini. Ocean models and observations of submarine termini suggest that plumes enhance melt and undercutting, leading to calving and potential glacier destabilization. Here we systematically evaluate how simulated plume structure and submarine melt during summer months depends on realistic ranges of subglacial discharge, glacier depth, and ocean stratification from 12 Greenland fjords. Our results show that grounding line depth is a strong control on plume‐induced submarine melt: deep glaciers produce warm, salty subsurface plumes that undercut termini, and shallow glaciers produce cold, fresh surface‐trapped plumes that can overcut termini. Due to sustained upwelling velocities, plumes in cold, shallow fjords can induce equivalent depth‐averaged melt rates compared to warm, deep fjords. These results detail a direct ocean‐ice feedback that can affect the Greenland Ice Sheet. Key Points: We simulate subglacial plumes and submarine melt in 12 Greenland fjords spanning grounding line depths from 100 to 850 m Deep glaciers produce warm, salty subsurface plumes that undercut ice; shallow glaciers drive cold, fresh surface plumes that can overcut Plumes in cold, shallow fjords can induce comparable depth‐averaged melt rates to warm, deep fjords due to sustained upwelling velocities